Perancangan Aplikasi Penggajian Karyawan Berbasis WEB Mengunakan Framework Codeigniter (Studi Kasus: Outlet Papoy Chicken) - Aldi Gilang Maulana (FKOM UNIKU, 2024)
Papoy chicken, a chicken restaurant in Tasikmalaya, is still facing management challenges, especially in the employee payroll process which is still done manually. This research aims to investigate the move from manual payroll to web application as a solution to increase the efficiency and accuracy of the payroll process at Papoy chicken. The research methods used include internal surveys, analysis of existing processes and development of web application prototypes for employee payroll. The research results show that the manual payroll process is prone to errors and takes up valuable time, by introducing a web application for employee payroll, Papoy chicken can reduce errors, save time and increase employee satisfaction. This web application will provide an intuitive interface and it is integrated with the internal management system, enabling managers to easily manage payroll information